MODERN METHODOLOGY OF LIQUIDITY AND SOLVENCY ANALYSIS OF THE ENTERPRISE - LOPATOVSKA, Oksana; PONOMAROVA, Кarina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the defined and characterized currently existing methods of researching the liquidity and solvency of domestic enterprises. According to the results of the research of numerous studies, the "most optimal" interpretations of the concepts of "liquidity" and "solvency" of the enterprise were determined according to the authors.The authors defined the purpose, tasks and functions of the analysis of liquidity and solvency of the enterprise. It was found that today the majority of domestic scientists propose to conduct their research in two directions: directly analyze the balance sheet of the enterprise and calculate a certain set of relative indicators (coefficients).For a more in-depth study of the company's liquidity and solvency, the authors of the article suggest using an analysis methodology that includes: 1) analysis of the company's balance sheet liquidity, by comparing assets grouped by the degree of liquidity with liabilities grouped by maturity; 2) assessment of the company's financial condition as of the reporting date, in the short- and long-term perspective with determination of the type of its sustainability: absolute, normal, pre-crisis (critical) and crisis; 3) calculation and analysis of the main indicators of liquidity (the amount of own working capital, coefficients of absolute, term and total liquidity, liquidity coefficients of reserves, funds in accounts, the ratio of payables and receivables, the mobility of assets and the ratio of assets); 4) calculation of indicators of current solvency (coefficients of securing current assets with own working capital, total solvency, financial leverage (risk), restoration (losses) of solvency, ratio of net current assets to net assets, share of payables in equity and receivables), integral indicator and the general indicator of solvency.Also, the authors suggest supplementing the analysis of the company's liquidity by calculating the value of the "working capital" indicator, which is determined by two methods "from below" and "from above".According to the authors, the analysis of the company's liquidity and solvency using this method will allow a consistent and thorough investigation of the company's means of payment and obligations, which will become a solid basis for the development of management decisions in the direction of increasing the company's solvency in particular and strengthening its financial discipline in general.
Keywords: assets; balance sheet; liabilities; ratios; liquidity; enterprise; solvency; financial analysis; financial reporting; financial condition